Controlled growth of ultrathin ferromagnetic β‐MnSe semiconductor. Issue 3 (19th January 2022) - Zou, Jingyun; Yang, Yumeng; Hu, Dianyi; Kang, Lixing; Zhu, Chao; Tian, Dan; Lv, Xiaodong; Kutty, Govindan; Guo, Yuxi; Xu, Manzhang; Li, Fengyu; Hong, Guo; et al.
Abstract: Two‐dimensional (2D) magnetic crystals with intrinsic ferromagnetism are highly desirable for novel spin‐electronic devices. However, the controllable synthesis of 2D magnets, especially the direct growth of 2D magnets on substrate surfaces, is still a challenge. Here, we demonstrate the synthesis of ultrathin zinc‐blende phase manganese selenide (β‐MnSe) nanosheets using the chemical vapor deposition (CVD) technique. The 2D β‐MnSe crystals exhibit distinct ferromagnetic properties with a Curie temperature of 42.3 K. Density functional theory (DFT) calculations suggest that the ferromagnetic order in β‐MnSe originates from the exchange coupling between the unsaturated Se and Mn atoms. This study presents significant progress in the CVD growth of ultrathin 2D magnetic materials by thinning bulk magnets, and it will pave the way for the building of energy‐efficient spintronic devices in the future. Abstract : Two‐dimensional magnetic crystals with intrinsic ferromagnetism are highly desirable for novel spin‐electronic devices. Ultrathin zinc‐blende phase manganese selenide (β‐MnSe) nanosheets were synthesized using the chemical vapor deposition technique. The exchange coupling between the unsaturated Se and Mn atoms generates the ferromagnetic order in β‐MnSe, making it a ferromagnetic semiconductor with a Curie temperature of 42.3 K.